2012
DOI: 10.4317/medoral.17778
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective clinicopathological study on oral lichen planus and malignant transformation: Analysis of 518 cases

Abstract: Objective: To investigate the epidemiological and clinical characteristics of a relatively large cohort of patients with oral lichen planus (OLP) from eastern China. Study design: A total of 518 patients with histologically confirmed OLP in a long-term follow-up period (6 months-21.5 years) were retrospectively reviewed in our clinic. Results: Of the 518 patients, 353 females and 165 males were identified. The average age at diagnosis was 46.3 years (range 9-81 years) with the buccal mucosa being the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
0
23

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 21 publications
10
70
0
23
Order By: Relevance
“…The topographic distribution of oral lesions is not uniform. In studies by Shen et al buccal mucosa was involved most frequently with 14.9 % [11]. The clinical morphology of MLP is diverse.…”
Section: Mucosal Lichen Planusmentioning
confidence: 98%
See 3 more Smart Citations
“…The topographic distribution of oral lesions is not uniform. In studies by Shen et al buccal mucosa was involved most frequently with 14.9 % [11]. The clinical morphology of MLP is diverse.…”
Section: Mucosal Lichen Planusmentioning
confidence: 98%
“…Oral MLP is a facultative precancerous lesion. In individual studies malignant transformation was observed in 0.4-3.7 or 5.3 % of cases [11,15,24]. A recent review article documented esophageal involvement by LP [25].…”
Section: Mucosal Lichen Planusmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of them had histological confirmation of all cases with distinguish between OLP and OLL [1,11,23,25,[27][28][29][30][31][32][33] and five presented with control group [11,13,24,25,27]. It can be noticed clear difference in reported coexistence of thyroid gland pathosis and OLP between Northern and Central European countries (Finland [11], Czech Republic [28] and Croatia [34]) and Southern Mediterranean countries (Italy [1,26] and Turkey [29]).…”
Section: Discussionmentioning
confidence: 99%